A Quintessentially English Glove Legacy - Turner, Frances Ann (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2019)
The English artisan skills required to produce exquisitely embellished, leather gloves is an important English legacy. The historic cities of Worcester and Bath have, since the 17th Century, been centres of craftsmanship for Glove makers and Design. There is something quintessentially English in the narrative of this heritage having strong connection to English culture and branding. Three important archival glove collections are housed in the Fashion Museum, Bath, the Museums Worcestershire collection and Dents Gloves. The paper will uncover the story of English glove design, manufacturing and social time whilst exploring the relevance of these collections for designers and makers today.